Factors Influencing the Flavour of Bovine Milk and Cheese from Grass Based versus Non-Grass Based Milk Production Systems - Kilcawley, Kieran N. (Foods, 2018)
There has been a surge in interest in relation to differentiating dairy products derived from pasture versus confined systems. The impact of different forage types on the sensory properties of milk and cheese is complex due to the wide range of on farm and production factors that are potentially involved. The main effect of pasture diet on the sensory properties of bovine milk and cheese is increased yellow intensity correlated to β-carotene content, which is a possible biomarker for pasture derived dairy products. Pasture grazing also influences fat and fatty acid content which has been implicated with texture perception changes in milk and cheese and increased omega-3 fatty acids. Changes in polyunsaturated fatty acids in milk and cheese due to pasture diets has been suggested may increase susceptibility to lipid oxidation but does not seem to be an issue to due increased antioxidants and the reducing environment of cheese. It appears that pasture derived milk and cheese are easier to discern by trained panellists and consumers than milk derived from conserved or concentrate diets. However, milk pasteurization, inclusion of concentrate in pasture diets, cheese ripening time, have all been linked to reducing pasture dietary effects on sensory perception. Sensory evaluation studies of milk and cheese have, in general, found that untrained assessors who best represent consumers appear less able to discriminate sensory differences than trained assessors and that differences in visual and textural attributes are more likely to be realized than flavour attributes. This suggests that sensory differences due to diet are often subtle. Evidence supports the direct transfer of some volatiles via inhalation or ingestion but more so with indirect transfer post rumen metabolism dietary components. The impact of dietary volatiles on sensory perception of milk and dairy products obviously depends upon their concentration and odour activity, however very little quantitative studies have been carried out to date. Some studies have highlighted potential correlation of pasture with enhanced “barny” or “cowy” sensory attributes and subsequently linked these to accumulation of p-cresol from the metabolism of β-carotene and aromatic amino acids or possibly isoflavones in the rumen. p-Cresol has also been suggested as a potential biomarker for pasture derived dairy products. Other studies have linked terpenes to specific sensory properties in milk and cheese but this only appears to be relevant in milk and cheese derived from unseeded wild pasture where high concentrations accumulate, as their odour threshold is quite high. Toluene also a product of β-carotene metabolism has been identified as a potential biomarker for pasture derived dairy products but it has little impact on sensory perception due to its high odour threshold. Dimethyl sulfone has been linked to pasture diets and could influence sensory perception as its odour threshold is low. Other studies have linked the presence of maize and legumes (clover) in silage with adverse sensory impacts in milk and cheese. Considerably more research is required to define key dietary related impacts on the flavour of milk and cheese.